A two-year follow-up study of risk of depression according to work-unit measures of psychological demands and decision latitude - Matias Brødsgaard Grynderup; Ole Mors; Åse Marie Hansen; Johan H Andersen; Jens Peter Bonde; Anette Kærgaard; Linda Kærlev; Sigurd Mikkelsen; Reiner Rugulies; Jane Frølund Thomsen; Henrik A Kolstad (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVES: The aim of this study was to examine if high psychological demands and low decision latitude at work increase the risk of depression. METHODS: In 2007, 4237 non-depressed Danish public employees within 378 different work units were enrolled in the study. Mean levels of psychological demands and decision latitude were computed for each work unit to obtain exposure measures that were robust to reporting bias. In 2009, 3046 (72%) participated at follow-up, and those reporting high levels of depressive, burnout or stress symptoms went through a psychiatric interview by which 58 cases of new onset depression were diagnosed. Odds ratios (OR) of depression for different levels of work unit mean psychological demands and decision latitude were estimated by logistic regression taking established risk factors into account. RESULTS: The OR for depression according to psychological demands was 1.07 [95% confidence interval (95% CI) 0.42-2.49] for every unit of change on a 5-point scale. The corresponding OR for decision latitude was 1.85 (95% CI 0.55-6.26). No interactive effects of psychological demands and decision latitude were observed. CONCLUSION: These findings suggest that low decision latitude may predict depression, but confidence intervals are wide and findings are also compatible with no increased risk.